Mitochondrial DNA haplogroups and serum levels of proteolytic enzymes in patients with osteoarthritis. Issue 4 (21st December 2010) - Rego-Pérez, I; Fernández-Moreno, M; Deberg, M; Pértega, S; Fernández-López, C; Oreiro, N; Henrotin, Y; Blanco, F J
Abstract : Objective: To analyse the influence of mitochondrial DNA haplogroups, as well as the radiographic grade, on serum levels of proteolytic enzymes in patients with osteoarthritis (OA). Methods: Serum levels of metalloproteinase-1 (MMP-1), MMP-3, MMP-13, myeloperoxidase and cathepsin K were analysed in 73 patients with OA and 77 healthy controls carrying the haplogroups J, U and H, by ELISA. Knee and hip radiographs were classified according to Kellgren and Lawrence (K/L) scoring from grade 0 to grade IV. Non-parametric and multiple regression analyses were performed to test the effects of clinical variables, including gender, age, smoking status, diagnosis, haplogroups and radiological K/L grade on serum levels of these enzymes. Results: A significant influence of the haplogroups on the serum levels of MMP-3 and MMP-13 was detected (p=0.027 and p=0.035, respectively). Patients with OA with haplogroup H showed higher serum levels of MMP-3 than healthy controls. Serum levels of MMP-13 were significantly higher in patients with OA (p<0.001), and carriers of the haplogroup J showed lower levels than H carriers. Besides, levels of MMP-13 were proportionally higher in radiological groups B (K/L grade II and III) and C (K/L grade IV) than in group A (K/L grade 0 and I) (p=0.005). Conclusions: This study shows that haplogroups have a significant influence on serum levels of MMP-3 and MMP-13. The influence of the haplogroups on serum levels of MMP-3 is clearly dependent on the diagnosis, whereas the influence of the haplogroups on serum levels of MMP-13 is independent of diagnosis.